Green function theory of anisotropic Heisenberg Ferromagnet with biquadratic exchange - Tiwari M.; Srivastava R.N. (My University, 2025)
The effects of biquadratic exchange interaction and the uniaxial anisotropy on the curie temperature of the Heisenberg Ferromagnet with spin-one has been studied. Green function technique with random phase approximation has been used. The variation of curie temperature with biquadratic and anisotropic parameters for different lattices has been discussed. © 1982 Springer-Verlag.